Fetal myocardial deformation in maternal diabetes mellitus and obesity. (May 2017) - Kulkarni, A.; Li, L.; Craft, M.; Nanda, M.; Lorenzo, J. M. M.; Danford, D.; Kutty, S.
ABSTRACT: Objective: Experimental evidence suggests that changes in the fetal myocardium result from intrauterine effects of maternal diabetes mellitus and obesity. The aim of this study was to assess fetal cardiac function using two‐dimensional speckle‐tracking echocardiography to determine the effects of maternal diabetes and obesity on the fetal myocardium. Methods: Comparative cross‐sectional evaluation of myocardial function in fetuses of mothers with diabetes mellitus (FDM) or obesity (FO) and normal gestational age‐matched control fetuses (FC) was performed using two‐dimensional speckle‐tracking echocardiography at two centers. Results: In total, 178 fetuses (82 FDM, 26 FO and 70 FC) met the enrolment criteria. Mean gestational age at assessment was similar among groups: 25.3 ± 5.1 weeks for FDM, 25.0 ± 4.6 weeks for FO and 25.1 ± 4.9 weeks for FC. Mean maternal body mass index was significantly higher in FDM and FO groups compared with the FC group. Statistically significant differences in fetal cardiac function were detected between FDM and FC for global longitudinal strain (mean ± SD, –21.4 ± 6.5% vs –27.0 ± 5.2%; P < 0.001), global circumferential strain (mean ± SD, –22.6 ± 6.5% vs –26.2 ± 6.8%; P = 0.002), average longitudinal systolic strain rate (median, –1.4 (interquartile range (IQR), –1.7 to –1.1)/s vs –1.6 (IQR, –2.0 to –1.4)/s; P = 0.001) and average circumferential systolic strain rate (median, –1.4 (IQR, –1.9 to –1.1)/s vs –1.6 (IQR, –2.1 to –1.3)/s; P = 0.006). Cases of non‐obese FDM also had abnormal strain parameters compared with FC. Global longitudinal strain (mean ± SD, –21.1 ± 7.5%) and average circumferential systolic strain rate (median, –1.3 (IQR, –1.8 to –1.1)/s) were significantly lower in FO compared with FC. Conclusions: Unfavorable changes occur in the fetal myocardium in response to both maternal diabetes mellitus and obesity. The long‐term prognostic implications of these changes require further study. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.